2014
DOI: 10.1175/mwr-d-12-00354.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Generating Initial Condition Perturbations in a Regional Ensemble Prediction System: Blending

Abstract: A blending method for generating initial condition (IC) perturbations in a regional ensemble prediction system is proposed. The blending is to combine the large-scale IC perturbations from a global ensemble prediction system (EPS) with the small-scale IC perturbations from a regional EPS by using a digital filter and the spectral analysis technique. The IC perturbations generated by blending can well represent both largescale and small-scale uncertainties in the analysis, and are more consistent with the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…The accurate prediction of CI is a problem that is highly sensitive to the interactions between the surface and free atmosphere that occur within the PBL (Stensrud, ). Previous mesoscale studies have also shown that low‐level jet, land‐sea breeze, mountain‐valley wind, and terrain effects within the PBL play important roles in the occurrence of warm‐sector heavy rainfall (Wang, Luo, et al, ; Wu & Luo, ; Wu et al, ). Thus, the practical predictability analysis of warm‐sector torrential rainfall in this section focuses mainly on the uncertainties in the PBL.…”
Section: Practical Predictability: Uncertainties In the Simulated Tormentioning
confidence: 98%
“…The accurate prediction of CI is a problem that is highly sensitive to the interactions between the surface and free atmosphere that occur within the PBL (Stensrud, ). Previous mesoscale studies have also shown that low‐level jet, land‐sea breeze, mountain‐valley wind, and terrain effects within the PBL play important roles in the occurrence of warm‐sector heavy rainfall (Wang, Luo, et al, ; Wu & Luo, ; Wu et al, ). Thus, the practical predictability analysis of warm‐sector torrential rainfall in this section focuses mainly on the uncertainties in the PBL.…”
Section: Practical Predictability: Uncertainties In the Simulated Tormentioning
confidence: 98%
“…Although the above results are mixed, these comparisons may shed some light on further improvement in present system. A practical way to take advantages of both ensemble perturbations is developing a blending technique, which has been primarily investigated by Caron [33] and Wang et al [34]. This technique can obtain blended perturbations that contain large-scale component from downscaling perturbations and small-scale component from ETKF perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…But the INCA system is also able to improve the pure NWP forecasts up to +48 h using topographical downscaling and error correction (through a rather The second component of En-INCA is ALADIN-LAEF, the limited area ensemble forecasting system developed at ZAMG in cooperation with LACE members. The latest ensemble specifications are summarized in Table 1, the overall method is described in detail in Wang et al (2011), and some of its components in Wang et al (2010Wang et al ( , 2014. A comprehensive validation of LAEF compared to a global ensemble prediction system is given by Wang et al (2012).…”
Section: The En-inca Systemmentioning
confidence: 99%
“…Focusing on regional and local patterns one can see considerable differences in frost probabilities, especially in the southern and eastern low lying areas of Austria, in the Waldviertel as well as in the far West of Austria (marked with colored polygons). Wang et al, 2014) In order to show the added value of En-INCA during the nowcasting period, Fig. 3c shows the INCA analysis of 2 m temperature for 31 December 2012, 05:00 UTC.…”
Section: Case Study and Validationmentioning
confidence: 99%